2019
DOI: 10.3390/ijerph16244912
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Arsenic Adsorption Behaviors of Water Treatment Residuals from Waterworks for Iron and Manganese Removal

Abstract: Water treatment residuals (WTRs), obtained from a groundwater treatment plant for biological iron and manganese removal, were investigated and used as adsorbents for arsenic removal. The surface morphology and structural features of the WTRs were characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray diffraction (XRD), and Brunauner–Emmett–Teller analysis (BET). Laboratory experiments were also carried out to test the adsorption capability and adaptability of WTRs on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 21 publications
(19 reference statements)
2
4
0
Order By: Relevance
“…Normally there are three stages during the adsorption processes in porous media (Zeng et al, 2019), in the case of samples PVA50/Alg50/Bent30 and PVA75/Alg25/Bent30 a similar result was obtained. In the first two hours, the first stage occurs where the adsorbate diffuses towards the adsorbent surface.…”
Section: Arsenic Removal Testssupporting
confidence: 68%
“…Normally there are three stages during the adsorption processes in porous media (Zeng et al, 2019), in the case of samples PVA50/Alg50/Bent30 and PVA75/Alg25/Bent30 a similar result was obtained. In the first two hours, the first stage occurs where the adsorbate diffuses towards the adsorbent surface.…”
Section: Arsenic Removal Testssupporting
confidence: 68%
“…Therefore, the adsorption kinetics of As 3+ and As 5+ from solution by the adsorbent Fe 3 O 4 @mZrO 2 -Re (Re = Y/La/Ce) is more suitably designated by the Pseudo-second-order reaction kinetic model, where rate of reaction depended directly on the square of the concentration of the reactants remaining in the solution [ 48 ]. Many other researchers suggested that adsorption kinetics of Magnetic nanomaterials are supporting the Pseudo-second order Kinetics, and our results are also favoring the 2nd order kinetic model [ 49 , 50 , 51 ].…”
Section: Resultssupporting
confidence: 81%
“…Previous studies have shown that iron oxides can be simply formed by the oxidation of Fe 2+ in natural water. However, due to the presence of other ions such as silica, calcium, or manganese, as well as organic matter in groundwater, the process of crystallization is constricted [ 35 , 36 ], which is demonstrated by the results of this study. Despite the high content of iron oxides, as demonstrated by XRF analysis, it was an amorphous form of iron compounds.…”
Section: Resultsmentioning
confidence: 81%
“…GWTRs-1 and 3 displayed a type II isotherm with a type H3 hysteresis loop ( Figure 4 ). This suits a mesoporous character with the construction of slit-shaped pores originating from the stacking of crystal particles [ 64 , 65 ], whereas GWTRs-2 and 3 had a composite of type IV isotherms with hysteresis loop of type H3, having adsorption curve characteristics of typical mesoporous material [ 36 ]. Table 3 shows the results of S BET and porosity analysis.…”
Section: Resultsmentioning
confidence: 99%